2022
DOI: 10.1021/acssuschemeng.2c01553
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of the cis/trans Stereochemistry of Limonene Oxides toward the Synthesis of Biobased Thermosets by Crosslinking with Anhydrides

Abstract: This study emphasizes the reactivity of (R)-(+)limonene, a major byproduct of the citrus industry, and its potential to be used as a biobased thermoset precursor. We separated the cis and trans limonene epoxides and synthesized limonene dioxide (LDO) monomers using an environmentally friendly epoxidation. Their crosslinking reactivity with glutaric anhydride, a biobased hardener, to obtain fully biobased thermosets was studied. The influence of the stereochemistry of limonene epoxide monomers on the copolymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…According to Table 4 and Figure , the vitrimer with the highest cross‐linking density (bV‐M 37 H 63 ‐15) exhibits the best mechanical properties, that is, σ m∅ = 15.9 MPa, ɛ m∅ = 84.0% because of the high cross‐linking density. [ 71,72 ] Similarly, it exhibits the highest T g and T 5% with the values of 55.3 and 224.7 °C (Figure S7, Supporting Information), indicating that the thermal properties are directly affected by the crosslink density. [ 73,74 ] Moreover, these vitrimers show τ 150 °C of 1.6–4.2 s, Gʹ (25 °C) of 0.242–1.075 GPa, and Gʹ rubber (180 °C) of 0.161–0.515 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…According to Table 4 and Figure , the vitrimer with the highest cross‐linking density (bV‐M 37 H 63 ‐15) exhibits the best mechanical properties, that is, σ m∅ = 15.9 MPa, ɛ m∅ = 84.0% because of the high cross‐linking density. [ 71,72 ] Similarly, it exhibits the highest T g and T 5% with the values of 55.3 and 224.7 °C (Figure S7, Supporting Information), indicating that the thermal properties are directly affected by the crosslink density. [ 73,74 ] Moreover, these vitrimers show τ 150 °C of 1.6–4.2 s, Gʹ (25 °C) of 0.242–1.075 GPa, and Gʹ rubber (180 °C) of 0.161–0.515 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained material presents T g of 90 °C, a high degradation temperature (270 °C) and good mechanical properties: σ =27 MPa; ϵ =3,5 %; E =1150 MPa; E’ =1650 MPa, SD=78 [50] . Following these results, we recently investigated the influence of cis‐ and trans ‐LDO stereochemistry on copolymerization with GA. For the first time we found that the cis ‐LDO generates thermosets with high mechanical properties (tan δ =116 °C, σ=43 MPa; ϵ=4.56 %; E=1.36 GPa; E’=1.68 GPa, Shore D hardness=81) [51] …”
Section: Introductionmentioning
confidence: 88%
“…[50] Following these results, we recently investigated the influence of cis-and trans-LDO stereochemistry on copolymerization with GA. For the first time we found that the cis-LDO generates thermosets with high mechanical properties (tan δ = 116 °C, σ = 43 MPa; ɛ = 4.56 %; E = 1.36 GPa; E' = 1.68 GPa, Shore D hardness = 81). [51]…”
Section: Copolymerization Of Limonene Dioxidementioning
confidence: 99%
“…It is typically abundant in citrus peels and obtained via extraction as a major byproduct of citrus production; the annually recovered amount exceeds 70,000 tons. , Limonene contains two isomeric alkene groups from isoprene units with distinct reactivity, each of which experiences characteristic functionalization or polymerization reactions . Thus, owing to their availability and synthetic flexibility, researchers have devoted much effort to developing limonene-based polymers as a form of polycarbonates or polyesters. Nonetheless, when processed into thermosets, limonene normally requires prior chemical modification such as epoxidation, and the resultant networks have been seldom endowed with a reversible nature so far; they are partially reusable or not. Therefore, it is beneficial to develop an accessible design for reusable thermosets using natural limonene without the need for pretreatment, which is achievable by diversification of polymer structures and introduction of suitable reversible chemistry and further expands the adaptability of limonene for sustainable materials.…”
Section: Introductionmentioning
confidence: 99%